THE EFFECTIVENESS OF THE COMMUNITY-BASED DRINKING WATER SUPPLY SYSTEM IN IMPROVING THE DEGREE OF PUBLIC HEALTH IN TALUAK VILLAGE, PARIAMAN CITY: EFEKTIVITAS SISTEM PENYEDIAAN AIR MINUM BERBASIS MASYARAKAT DALAM MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT DI DESA TALUAK KOTA PARIAMAN - Mia Rista; Aldri Frinaldi (SOSIOEDUKASI, 2024)
The level of public health is a measure that reflects the health condition of a population or community determined by environmental factors, behavior, health services and heredity. Environmental and behavioral factors also play a major role in determining water quality, which directly impacts the level of public health. Therefore, it is important to implement a community-based Drinking Water Supply System (SPAM) program, including in Pariaman City, to improve public health status and prevent health impacts. This study aims to analyze how SPAM can impact the level of public health in Taluak Village, Pariaman City. Providing access to clean water and encouraging the community to be active in drinking water management are the program objectives. The background of this research is that SPAM has not been optimal in improving the health status of the community in Taluak Village, Pariaman City and there are health impacts for the community. This type of research is qualitative using a descriptive approach and the selection of informants using purposive sampling technique. The results showed that SPAM in Taluak Village has helped improve access to clean water and reduce the risk of diarrhea and skin infections. However, SPAM faces challenges, such as the lack of financial resources and the lack of community participation in maintaining the water infrastructure. From the results above, it can be concluded that the application of SPAM in improving public health in Taluak Village, Pariaman City is not yet optimal.